Feedback can provide information about learning progress - Joko Suriono; Slamet Widodo (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2023)
Education through entreprise is functioned to help students to bacome more entrepreneurial by facilitating real experience of managing entrepreneurial tasks or project (Pepin, 2012). Project-based assignments has become the means of entrepreneurial competence enhancement which is iterative, experimental, and treated as a process of practice (Man, 2012; Neck & Greene, 2011).